Together we survive : cultural and civilisational connectivity in the SAARC region - Saccidānandan, 1946-; Foundation of SAARC Writers and Literature (India) (New Delhi : Foundation of SAARC Writers and Literature, 2010)
Contributed essays.
Keywords: Collective memory and literature -- South Asia; South Asia -- Civilization